2021
DOI: 10.1590/pboci.2021.090
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour Management of the Contemporary Child in Paediatric Dentistry: An Overview of the Research

Abstract: Objective: To provide an overview of the most relevant studies on non-pharmacological behaviour management techniques for contemporary children, the so-called alpha generation, who undergo dental treatment. Material and Methods: A systematic search was performed on the Medline/PubMed and Google Scholar (grey literature) databases. The articles were read and data collected by two reviewers on an independent basis. Two reviewers collected data from the studies selected in tables structured by using the Rayyan QC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 30 publications
(40 reference statements)
0
4
0
Order By: Relevance
“…This could be attributed to technique's ability to engage children's attention, thus occupying their thoughts away from the procedure and minimizing unpleasant stimuli from the dental environment. This is in accordance with previous systematic reviews, which reported a positive effect of different distraction techniques on behavior alteration during dental treatment [6,11,[78][79][80]. Their full commitment to the distraction technique could be also associated to the reduction of treatment's duration reported in our review.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This could be attributed to technique's ability to engage children's attention, thus occupying their thoughts away from the procedure and minimizing unpleasant stimuli from the dental environment. This is in accordance with previous systematic reviews, which reported a positive effect of different distraction techniques on behavior alteration during dental treatment [6,11,[78][79][80]. Their full commitment to the distraction technique could be also associated to the reduction of treatment's duration reported in our review.…”
Section: Discussionsupporting
confidence: 93%
“…Acceptable effectiveness was reported for PP in eliminating children's fear and anxiety. Nowadays, there is a tendency for parents to be present in the operating room during treatment, which can be explained by today's life-style and parent's increased active involvement in the successful implementation of treatment [79]. Although, the above assumption is based on limited evidence and without a meta-analysis to allow specific conclusions to be drawn.…”
Section: Discussionmentioning
confidence: 99%
“…One of the forms of this distraction is through a system of glasses that is placed in the child's eyes, allowing them to connect to various devices so that they can choose their favorite animation, aligned with their age group (CUNNINGHAM et al, 2021). The personalization of this choice provides the infant patient with a sense of familiarity during the procedure, reducing the chances of uncooperative behavior (LIU et al, 2019;SILVA et al, 2021).…”
Section: Audio-visual Distractionsmentioning
confidence: 99%
“…A study evaluating clinical anxiety highlighted a significant reduction in anxiety during dental procedures, including during the injection of local anesthesia, in the group that used audiovisual distraction compared to the group without this technique, indicating the effectiveness of this approach in reducing fear and anxiety in dental care (GUJJAR et al, 2019;SILVA et al, 2021). Audio-visual glasses have been shown to be more efficient in promoting cooperative behavior and reducing anxiety, surpassing relaxation techniques such as music or TV in the dental environment (LIU et al, 2019).…”
Section: Audio-visual Distractionsmentioning
confidence: 99%
See 1 more Smart Citation